Fabrication and characterization of supercapacitor electrode by 3D printing - Dung, Hoang Tran; Ngo Thanh Dung; Trinh Quang Dung; Doan Thanh Tung; Nguyen Thi Yen; Le Thi Thanh Tam; Tran Viet Thu; Phan Ngoc Hong; Le Trong Lu (Vietnam Journal of Science and Technology, 2018)
Herein, we presents a study on the fabrication and characterization of supercapacitor electrode by 3D printing. A colloidal suspension containing carbon nanotubes (CNTs) and cobalt ferrite nanoparticles (CoFe2O4 NPs) was used as ink. The ink was successfully printed on aluminium substrate using a modified 3D printer followed by solvent evaporation to form a porous CNTs/CoFe2O4 aerogel film. The characterization results showed that the film has porous surface, high electrical conductivity and good electrochemical properties, indicating its promising application as supercapacitor electrode for energy conversion and storage.